2015
DOI: 10.1016/j.tranon.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative C-Reactive Protein/Albumin Ratio Predicts Prognosis of Patients after Curative Resection for Gastric Cancer

Abstract: BACKGROUND: An elevated preoperative C-reactive protein/albumin (CRP/Alb) ratio has been reported to be associated with a poor prognosis for hepatocellular carcinoma. The aim of the present study was to investigate the prognostic value of the preoperative CRP/Alb ratio and compare it with other systemic inflammatory response markers in patients with gastric cancer (GC). METHODS: A retrospective study was performed in 455 patients with GC undergoing curative resection. We investigated the correlations between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
166
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(187 citation statements)
references
References 39 publications
15
166
0
6
Order By: Relevance
“…The CRP/Alb ratio is a useful prognostic indicator that was initially used to identify patients with serious conditions on an acute medical ward by Fairclough et al (41). Subsequently, multiple studies have demonstrated that the CRP/Alb ratio exhibited prognostic value in numerous types of cancer (15)(16)(17)(18)42). The present study revealed that a high CRP/Alb ratio indicated increased tumor invasion and metastasis and poorer prognosis compared with a low CRP/Alb ratio.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The CRP/Alb ratio is a useful prognostic indicator that was initially used to identify patients with serious conditions on an acute medical ward by Fairclough et al (41). Subsequently, multiple studies have demonstrated that the CRP/Alb ratio exhibited prognostic value in numerous types of cancer (15)(16)(17)(18)42). The present study revealed that a high CRP/Alb ratio indicated increased tumor invasion and metastasis and poorer prognosis compared with a low CRP/Alb ratio.…”
Section: Discussionmentioning
confidence: 52%
“…Although the prognostic value of the CRP/Alb ratio and NLR in GC has been reported previously (42,50), to the best of our knowledge, the present study is the first to report that the that the combination of the CRP/Alb ratio and NLR is associated with significant prognostic value and may further stratify prognosis compared with using single indicators.…”
Section: Discussionmentioning
confidence: 54%
“…On the other hand, another inflammation-related biomarker, the blood C-reactive protein (CRP)-to-albumin ratio (CAR), has also been reported to be a good prognostic factor in various cancer types (9)(10)(11)(12)(13)(14)(15). In some of these studies, CAR and NLR were assessed simultaneously, and both of them were reported to be prognostic factors for OS in patients with operable non-small cell lung cancer and those with unresectable metastatic colorectal cancer (9,11).…”
Section: The Prognostic Utility Of the Pretreatment Blood Neutrophiltmentioning
confidence: 99%
“…5 Liu et al, reported a significant correlation of decreased albumin and increased CRP levels with shorter survival, and CRP/albumin ratio as an independent prognostic marker, particularly in cases with Stage I and Stage III disease. 7 The authors proved that this ratio might be related to the nutritional status; but they could not demonstrate its correlation with weight loss and body mass index. Administration of anti-inflammatory therapy and nutritional support was also recommended for cases with increased CRP/albumin ratio.…”
Section: Discussionmentioning
confidence: 92%
“…7 There are studies which show correlation between proliferative activity and systemic inflammatory response associated with the tumor. 8 Hypoalbuminemia is a typical index of malnutrition and has been associated with poor prognosis in patients with advanced cancers.…”
Section: Discussionmentioning
confidence: 99%